2005
DOI: 10.2519/jospt.2005.35.2.72
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial Impingement Syndrome: The Effect of Changing Posture on Shoulder Range of Movement

Abstract: Study Design: Random allocation of subjects into a placebo-controlled, crossover study. Objectives: To investigate the effect of changing thoracic and scapular posture on shoulder flexion and scapular plane abduction range of motion in asymptomatic subjects, and in subjects with subacromial impingement syndrome. Background: Changes in upper body posture and concomitant imbalance of the muscle system have been proposed as one of the etiological mechanisms leading to subacromial impingement syndrome. Although cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(129 citation statements)
references
References 79 publications
3
115
0
7
Order By: Relevance
“…thoracic kyphosis, forward head posture, intersegmental locking, or hypomobility of the upper thoracic spine) is related to changes in the position of the scapula, and an imbalance of the scapulothoracic muscles. It is suggested that spinal alignment has a great influence on the scapular position and shoulder range of motion (Lewis, Wright, & Green, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…thoracic kyphosis, forward head posture, intersegmental locking, or hypomobility of the upper thoracic spine) is related to changes in the position of the scapula, and an imbalance of the scapulothoracic muscles. It is suggested that spinal alignment has a great influence on the scapular position and shoulder range of motion (Lewis, Wright, & Green, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, six participants had both shoulders assigned to the experimental condition, three had both shoulders assigned to the control condition, and 19 had one shoulder in each condition. Sagital plane scapular position has been demonstrated to vary between asymptomatic and symptomatic subjects with a difference between mean seated RSP of 7 AE 2.5e3.2 mm respectively (Lewis et al, 2005). Scapular position has been shown to…”
Section: Study Samplementioning
confidence: 98%
“…The overall postural awareness was taught with chin tuck and scapular retraction to promote an erect posture. [43][44][45] Cold pack gel application on the shoulder was recommended to control pain 5 times a day, especially before and after exercises. 46,47 They were treated in the outpatient physical therapy unit once a week for 6 weeks.…”
Section: Designmentioning
confidence: 99%